2017
DOI: 10.1016/j.joco.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of azithromycin versus trimethoprim/sulfamethoxazole in treatment of toxoplasmic retinochoroiditis

Abstract: PurposeTo assess the efficacy of oral azithromycin in the treatment of toxoplasmic retinochoroiditis.MethodsA randomized interventional comparative study was conducted on 14 patients with ocular toxoplasmosis who were treated with oral azithromycin and 13 patients who were treated with oral trimethoprim/sulfamethoxazole for 6–12 weeks. The achievement of treatment criteria in the two groups and lesion size reduction were considered as primary outcome measures.ResultsThe resolution of inflammatory activity, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Adverse effects were, however, more commonly reported in the pyr-sulf group. Similarly, a recent small, randomized trial of 27 patients showed equivalent efficacies of oral azithromycin (500 mg followed by 250 mg daily) plus steroids and oral TMP-SMX (160/800 mg twice daily) plus steroids in decreasing retinal lesion size, clearing vitreous inflammation, and improving visual acuity after 6 to 12 weeks of treatment (134).…”
Section: Ocular Toxoplasmosismentioning
confidence: 84%
“…Adverse effects were, however, more commonly reported in the pyr-sulf group. Similarly, a recent small, randomized trial of 27 patients showed equivalent efficacies of oral azithromycin (500 mg followed by 250 mg daily) plus steroids and oral TMP-SMX (160/800 mg twice daily) plus steroids in decreasing retinal lesion size, clearing vitreous inflammation, and improving visual acuity after 6 to 12 weeks of treatment (134).…”
Section: Ocular Toxoplasmosismentioning
confidence: 84%
“…Chang et al, (1988), Neville et al, (2015) and Lashay et al, (2017) showed the inhibitory effect of roxithromycin, azithromycin and spiramycin on T. gondii in-vitro 24,30,31 . The effect of macrolide antibiotics on T. gondii in-vivo and in-vitro has been investigated by researchers in numerous studies and the beneficial effect of these antibiotics in the treatment of toxoplasmosis has been proved in them.…”
Section: Discussionmentioning
confidence: 99%
“…AZM was found to be an acceptable alternative to trimethoprim/sulfamethoxazole in terms of reducing the size of retinal lesions and improving vision. 23 Pyrimethamine and AZM in comparison with pyrimethamine and sulfadiazine were of similar efficacy, but the safety profile (frequency and severity of side effects) was significantly better in the regiment which contained AZM. 55 Likewise, the triple combination of trimethoprim/sulfamethoxazole and AZM was found safe, effective, and it seemed to hasten the resolution of inflammation.…”
Section: Toxoplasmosismentioning
confidence: 92%